Effective classroom questioning - Goodwin, Stephanie S.; Sharp, Gregory W.; Cloutier, Edward F.; Diamond, Nancy A.; Universiti Teknologi Malaysia. Unit Pengajaran dan Pembelajaran (Sekudai : UNIPEN, 1994)
44